Designing the Bala Anjani alternate universe through the integration of Sasak cultural heritage and gender equality narratives - Nahdlatuzzainiyah Nahdlatuzzainiyah; Ni Ketut Putri Nila Sudewi; Haryono Haryono (Institut Seni Indonesia Surakarta, 2026)
The Bala Anjani dance is a traditional performing art from Lombok that embodies values of women’s empowerment and gender equality. Previous studies have adapted Bala Anjani into webtoon characters; however, these adaptations were limited to a single storyline and did not support sustainable narrative development. Moreover, studies on Alternate Universe (AU) have primarily focused on fan fiction and literary works, with limited application to traditional performing arts. This study aims to design an AU for the Bala Anjani webtoon by integrating Sasak cultural heritage and gender equality narratives. The novelty of this study lies in applying the AU approach to expand a traditional dance-based narrative into five interconnected story worlds that enable broader cultural exploration and diverse gender representations. Using a qualitative and design-based approach, data were collected through observation, interviews, documentation, and literature review, while the design process employed a modified Design Thinking model. The study produced five alternative story synopses and character designs incorporating Sasak cultural elements such as songket, traditional textiles, keris, and klewang. Expert validation and user testing indicated that the designs were culturally relevant, gender-sensitive, visually feasible, and positively received by young readers.